Transition to E - Learning : By Choice or By Force – A Cross - Cultural and Trans-National Assessment - Dash, Ganesh; Chakraborty, Debarun (Prabandhan: Indian Journal of Management, 2021)
Purpose : This study focused on the transition to e-learning in these turbulent times and its adaptation mode. The study aimed to measure teachers' and students' satisfaction and adoption levels towards e-learning in KSA and India due to the COVID-19 pandemic. In a nutshell, we intended to address three primary research questions: What were the factors affecting the satisfaction and adoption level of teachers & students towards e-learning during the COVID-19 pandemic? Does choice moderate the associations between perceived usefulness, perceived ease of use, satisfaction, and behavioral intention to use? Does satisfaction mediate the relationship between perceived usefulness, perceived ease of use, and behavioral intention to use? Methodology : Four hundred seventy-six faculty members and students from KSA and India were considered as the sample. A structured questionnaire was used to collect the data, and structural equation modeling was used to analyze the same. Findings : The findings suggested that Perceived Usefulness (PU) had a significant impact on Satisfaction (SAT) and Behavioural Intention to Use (BIU). Perceived Ease of Use (PEU) did not have a substantial effect on Satisfaction (SAT), but had a significant impact on Behavioural Intention to Use (BIU). Further, Satisfaction (SAT) and Choice (CHO) too had a substantial effect on Behavioural Intention to Use (BIU). Satisfaction (SAT) mediated the relationship between Perceived Ease of Use (PEU) and Behavioural Intention to Use (BIU). Again, Choice (CHO) moderated the relationship between Perceived Ease of Use (PEU) and Behavioural Intention to Use (BIU). Originality : This study was unique in comparing the impact of different cultures, economies, and governance models on this transition to e-learning. It provided a cross-cultural, trans-national, and cross-sectional analysis with a futuristic e-learning framework.